REVOCATION OF RIGHTS TO BE ELECTED AND VOTE FOR A CONVICTED OF CORRUPTION - Denny Ardiansyah (IJCLS (Indonesian Journal of Criminal Law Studies), 2017)
The criminal act of corruption is a criminal act that has an extra ordinary impact on the stability of the nation and state. Because the impact of these crimes is very systemic and make enormous losses in the state finance sector. Some cases occurred an ex-convict corruption case, when it was out of running his penalty, it turns out to be more officials in the environment of his service. The purpose of this study is first to examine or analyze the formulation policy of revocation of the right to be elected and vote for convicted corruption, secondly To review or analyze the policies that can be applied in the formulation in the future. The research method used in this legal research is juridical-normative, with a policy-oriented approach. The model of analysis is Juridical Comparative, and also conducts Prescriptive Juridical Analysis. The first result of research Whereas basically the regulation concerning additional crime in the form of revocation of certain rights including the right to be elected and vote has been regulated in criminal code (KUHP) and constitution No 31 of 1999 about eradication of corruption crime. Secondly that although there has been renewal in RUU KUHP (Draft of Criminal Code) 2012 on additional criminal provisions can stand on its own, but with regard to the right to vote and to be elected is still unclear, so there is still a gap for criminals who finish criminal can become public officials again.